Physicochemical evaluation of guandul (Cajanus cajan (L) Millsp.) cultivated at Sibarco, Baranoa, Colombia - Valle-Mora , Alexis; Donado-Palacio, Francisco-Javier; Polo-Rodríguez, Laura-Vanessa (Revista Colombiana de Investigaciones Agroindustriales, 2020)
The aim of this research was to compare three cultural denominations of pigeon pea (Cajanus cajan (L) Millsp.) named cuarentano, siete granos y mojarrita, cropped at Sibarco, Baranoa, Atlántico department, Colombia. The gastronomic characteristics for cooking temperatures and times were evaluated at 95ºC to 105ºC and 0´-15´, 15´-30´ and 30´-37´, respectively. The different cultural denominations of pigeon pea did not show differences. In the physicochemical analysis, the moisture, ash, fat content, crude fibre and protein parameters were evaluated. A one-way analysis of variance "ANOVA" was performed at 95% confidence between pairs of means of the three denominations in each of the parameters. The statistical analysis showed that the only parameter that did not present a significant difference was crude fibre. The parameters for fat content, moisture, protein, ashes showed statistically significant differences. Multiple range test was applied to observe the behaviour of pair means that differ from each other, and to analyze the set of means in a total of the denominations against each parameter. The findings allowed to identify that there are means that differ in these parameters and that the analysis of the means as a whole did not show a significant difference at 95% confidence.